Penerapan Metode Cooperative Tipe Jigsaw dalam Meningkatkan Keaktifan Belajar Siswa Kelas V pada Pembelajaran Bahasa Indonesia di SD Negeri 03 Sidigede Kecamatan Welahan Kabupaten Jepara - Kinesti, Rakanita Dyah Ayu; Fatatussa’diyah, Fatatussa’diyah (Lembaga Yasin AlSys, 2023)
Researchers focus on conducting research in increasing the activeness of learning using the Jigsaw Type Cooperative learning method in learning Indonesian. The research was conducted to 1) find out the process of learning activities with the jigsaw cooperative learning method to increase the learning activity of fifth grade students in learning Indonesian. 2) Knowing the application of the cooperative type jigsaw method in increasing the learning activity of fifth grade students in learning Indonesian. This research method uses a type of qualitative research with a qualitative descriptive approach. The data sources used are primary and secondary data sources. Data collection techniques used in this research are observation, interviews, documents, and documentation. As for testing the validity of the data using source triangulation, technical triangulation, and time triangulation. Furthermore, researchers used data analysis in the form of data reduction, data presentation (data display), and drawing conclusions. The results of this study indicate that (1) the process of learning activities of the jigsaw cooperative learning method in the Indonesian language subject at SD Negeri 03 Sidigede Welahan Jepara goes through the stages of preparing the teacher to prepare a Learning Implementation Plan (RPP) and implementing the learning process with explanations The material presented includes preliminary activities, core activities, closing activities, evaluation activities, and assessment activities. (2) In applying the jigsaw type cooperative learning method, the teacher provides mastery of the material to students, namely in the form of evaluating the questions in thematic books in groups. It can be seen in the application of the cooperative type jigsaw method at SD Negeri 03 Sidigede that students listen to discussions well, can know the abilities of each individual, during discussions students ask each other questions and opinions, all students play an active role, accept each other's deficiencies in differences of opinion from the results of their friends' answers, students dare to solve problems, deeper understanding, all students are enthusiastic about doing assignments.